The influence of income and hours of work on first birth timing for Australian men and women - Kingsley, Meg (My University, 2016)
There is inequality in first family formation in Australia. It is important to understand inequality in first-birth timing because it is related to multigenerational disadvantage. This study investigates how income, as an indicator of inequality, is related to age at first birth, and how accounting for work hours affects the relationship. Using Australian panel data, and Cox regression models with time varying effects, this study examines the effect of income and hours of work on the hazard of first birth for females and males. The influence of gross weekly wages on the hazard of first birth is found to depend on age, with low incomes increasing the hazard at younger ages and higher incomes increasing the hazard at older ages. However, hours of work are found to influence first birth timing, indicating that working longer hours may be affecting the results. The relationship between income and first-birth timing changes once the influence of hours of work is removed, and hourly wages are examined instead. For men the pattern changes substantially with low incomes associated with higher first-birth risks at all ages. The results show that working longer hours for low wages confounds the effects of gross weekly wages on first-birth timing. The results suggest that there is inequality, as measured by labour income, in the timing of first family formation in Australia, and that including work hours is helpful in understanding the nature of this inequality. The study also highlights gender differences in the relationship between income and first-birth timing.
Keywords: Income & Finance; Families -- Fertility; Employment -- Work/life Balance; Culture -- Inequality; Employment; Labour market; Income, wealth and finances; Families and relationships; Families; Income & Finance; Employment; Culture; Fertility; Inequality; Work/life Balance; Families and relationships; Income, wealth and finances; Employment and unemployment